2016
DOI: 10.3727/152599516x14643674421771
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Perceived Functions of and Attitude Toward Corporate Sponsors of Small-scale Amateur Sporting Events

Abstract: Aspiring to become a sporting nation, one recommendation from Singapore's Vision 2030 is to develop a sustainable resourcing model by encouraging more corporate companies to sponsor sporting events. This research aimed to identify the perceived functions of corporate sponsors, which influenced consumers to develop positive attitudes toward these sponsors. A total of 210 undergraduate students participated in this study. The five perceived functions of corporate sponsors were ubiquity, sincerity, credibility, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Future studies could explore the role of event types on influencing the strength of effects in view of individual preferences and brand-event fit (X. T. B. Low & Pyun, 2016;Wohlfeil & Whelan, 2006). Regarding the effects of consumers' attitudes on behavioral intentions, future studies might consider additional constructs for analysis as suggested in previous studies which explored the Theory of Reasoned Action in the context of tourism and events (Han et al, 2010;Prayag et al, 2013;Quintal et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies could explore the role of event types on influencing the strength of effects in view of individual preferences and brand-event fit (X. T. B. Low & Pyun, 2016;Wohlfeil & Whelan, 2006). Regarding the effects of consumers' attitudes on behavioral intentions, future studies might consider additional constructs for analysis as suggested in previous studies which explored the Theory of Reasoned Action in the context of tourism and events (Han et al, 2010;Prayag et al, 2013;Quintal et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that participants' intention to revisit and recommend the event depended on their perceptions of the event image and their satisfaction with the event. In addition to the previous research focusing on the events themselves (e.g., event quality or event image), Low and Pyun ( 2016 ) emphasized the importance of the sponsor's characteristics (e.g., sincerity, credibility), and believed that the outstanding characteristics can enhance a positive attitude toward sponsorship activities, such as sports sponsorship of local and amateur colleges (Ko et al, 2017 ; Su and Chen, 2020 ; Su and Lai, 2021 ; Su and Wu, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Meenaghan ( 2001 ), a successful sports sponsorship event can provide consumers with a good impression of sponsors, thereby increasing the awareness and recognition of sponsored brands. Therefore, a small sponsorship event is a valuable practice for small-sized companies or newly established brands, such as small-scale amateur (Low and Pyun, 2016 ) and small-scale marathon events (Koo et al, 2014 ). Such events can also encourage community residents who are amateur players to participate in the activity, which will provide more exposure opportunities for sponsoring brands.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to large-scale sports events, small-scale amateur sporting events, including grassroots events, can also leave positive impacts on the local community [30,31]. As amateur events, grassroots sports are generally more manageable because they are smaller and require less financial and infrastructural support because they tap into existing resources and infrastructure [32]. They are also far less controversial than large-scale or mega events.…”
Section: Definition and Impact Of Sports Eventsmentioning
confidence: 99%